Difference between revisions of "009A Sample Final 1, Problem 2"
Jump to navigation
Jump to search
(2 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
<span class="exam"> Consider the following piecewise defined function: | <span class="exam"> Consider the following piecewise defined function: | ||
− | + | ::<math>f(x) = \left\{ | |
\begin{array}{lr} | \begin{array}{lr} | ||
x+5 & \text{if }x < 3\\ | x+5 & \text{if }x < 3\\ | ||
Line 8: | Line 8: | ||
\right. | \right. | ||
</math> | </math> | ||
− | + | <span class="exam">(a) Show that <math style="vertical-align: -5px">f(x)</math> is continuous at <math style="vertical-align: 0px">x=3.</math> | |
− | + | <span class="exam">(b) Using the limit definition of the derivative, and computing the limits from both sides, show that <math style="vertical-align: -3px">f(x)</math> is differentiable at <math style="vertical-align: 0px">x=3</math>. | |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''1.''' <math style="vertical-align: -5px">f(x)</math> is continuous at <math style="vertical-align: 0px">x=a</math> if |
|- | |- | ||
− | | | + | | <math style="vertical-align: -14px">\lim_{x\rightarrow a^+}f(x)=\lim_{x\rightarrow a^-}f(x)=f(a).</math> |
|- | |- | ||
− | |'''2.''' The definition of derivative for <math style="vertical-align: -5px">f(x)</math>& | + | |'''2.''' The definition of derivative for <math style="vertical-align: -5px">f(x)</math> is |
+ | |- | ||
+ | | <math style="vertical-align: -13px">f'(x)=\lim_{h\rightarrow 0}\frac{f(x+h)-f(x)}{h}.</math> | ||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 29: | Line 32: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We first calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x).</math> We have | + | |We first calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x).</math> We have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\lim_{x\rightarrow 3^+}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^+} 4\sqrt{x+1}}\\ | \displaystyle{\lim_{x\rightarrow 3^+}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^+} 4\sqrt{x+1}}\\ | ||
&&\\ | &&\\ | ||
Line 44: | Line 47: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^-}f(x).</math> We have | + | |Now, we calculate <math style="vertical-align: -14px">\lim_{x\rightarrow 3^-}f(x).</math> We have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\lim_{x\rightarrow 3^-}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^-} x+5}\\ | \displaystyle{\lim_{x\rightarrow 3^-}f(x)} & = & \displaystyle{\lim_{x\rightarrow 3^-} x+5}\\ | ||
&&\\ | &&\\ | ||
Line 59: | Line 62: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |Now, we calculate <math style="vertical-align: -5px">f(3).</math> We have | + | |Now, we calculate <math style="vertical-align: -5px">f(3).</math> We have |
|- | |- | ||
| | | | ||
− | + | <math>f(3)=4\sqrt{3+1}\,=\,8.</math> | |
+ | |- | ||
+ | |Since | ||
|- | |- | ||
− | | | + | | <math style="vertical-align: -15px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),</math> |
+ | |- | ||
+ | |<math style="vertical-align: -5px">f(x)</math> is continuous at <math style="vertical-align: 0px">x=3.</math> | ||
|} | |} | ||
Line 72: | Line 79: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We need to use the limit definition of derivative and calculate the limit from both sides. | + | |We need to use the limit definition of derivative and calculate the limit from both sides. So, we have |
− | |||
− | |||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^-}\frac{(3+h)+5-8}{h}}\\ | \displaystyle{\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^-}\frac{(3+h)+5-8}{h}}\\ | ||
&&\\ | &&\\ | ||
Line 94: | Line 99: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^+}\frac{4\sqrt{3+h+1}-8}{h}}\\ | \displaystyle{\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h}} & = & \displaystyle{\lim_{h\rightarrow 0^+}\frac{4\sqrt{3+h+1}-8}{h}}\\ | ||
&&\\ | &&\\ | ||
Line 116: | Line 121: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |Since | + | |Since |
|- | |- | ||
− | |<math style="vertical-align: -5px">f(x)</math>& | + | | <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math> |
+ | |- | ||
+ | |<math style="vertical-align: -5px">f(x)</math> is differentiable at <math style="vertical-align: 0px">x=3.</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)''' Since <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),~f(x)</math>  is continuous. | + | | '''(a)''' Since <math style="vertical-align: -14px">\lim_{x\rightarrow 3^+}f(x)=\lim_{x\rightarrow 3^-}f(x)=f(3),~f(x)</math>  is continuous at <math style="vertical-align: 0px">x=3.</math> |
|- | |- | ||
− | |'''(b)''' Since <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math> | + | | '''(b)''' Since <math style="vertical-align: -14px">\lim_{h\rightarrow 0^-}\frac{f(3+h)-f(3)}{h}=\lim_{h\rightarrow 0^+}\frac{f(3+h)-f(3)}{h},</math> |
|- | |- | ||
| | | | ||
− | + | <math style="vertical-align: -5px">f(x)</math>  is differentiable at <math style="vertical-align: 0px">x=3.</math> | |
|} | |} | ||
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 08:07, 10 April 2017
Consider the following piecewise defined function:
(a) Show that is continuous at
(b) Using the limit definition of the derivative, and computing the limits from both sides, show that is differentiable at .
Foundations: |
---|
1. is continuous at if |
2. The definition of derivative for is |
Solution:
(a)
Step 1: |
---|
We first calculate We have |
|
Step 2: |
---|
Now, we calculate We have |
|
Step 3: |
---|
Now, we calculate We have |
|
Since |
is continuous at |
(b)
Step 1: |
---|
We need to use the limit definition of derivative and calculate the limit from both sides. So, we have |
|
Step 2: |
---|
Now, we have |
|
Step 3: |
---|
Since |
is differentiable at |
Final Answer: |
---|
(a) Since is continuous at |
(b) Since |
is differentiable at |